Midtrimester transvaginal ultrasound cervical length screening for spontaneous preterm birth in diamniotic twin pregnancies according to chorionicity. (October 2018) - Roman, Amanda; Saccone, Gabriele; Dude, Carolynn M.; Ward, Andrew; Anastasio, Hannah; Dugoff, Lorraine; Zullo, Fulvio; Berghella, Vincenzo
Abstract: Objective: To compare the mean transvaginal ultrasound (TVU) cervical length (CL) at midtrimester screening for spontaneous preterm birth in asymptomatic monochorionic diamniotic versus dichorionic diamniotic twin pregnancies Study design: This was a multicenter retrospective cohort study. Study subjects were identified at the time of a routine second trimester fetal ultrasound exam at 18 0/7–23 6/7 weeks gestation. We excluded women that received progesterone, pessary, or cerclage. Distribution of CL was determined and normality was examined. Mean of TVU CL were compared between monochorionic diamniotic and dichorionic diamniotic pregnancies. The relationship of TVU CL with gestational age (GA) at delivery and incidence of spontaneous preterm birth (SPTB) at different TVU CL cut offs were assessed. Incidence of short TVU CL, defined as TVU CL ≤30 mm, was also calculated in the two groups. Results: 580 women with diamniotic twin pregnancies underwent TVU CL screening between 18 0/6 and 23 6/7 weeks. 175 (30.2%) were monochorionic diamniotic pregnancies, and 405 (69.8%) were dichorionic pregnancies. The demographic characteristics were similar on both groups. The mean GA at TVU CL was about 20 week in both groups. The mean TVU CL was significantly lower in the monochorionic diamniotic (32.8 ± 10.1) compared to the dichorionic (34.9 ± 8.6) group (MD −2.10 mm, 95% CI −3.91 to −0.29). TVU CL ≤30 mm was 16.6% (29/175) in the monochorionic group, and 11.9% (48/405) in the dichorionic group (aOR 1.48, 95% CI 1.03–2.43). Twins with a monochorionic diamniotic pregnancy had a significantly higher incidence of SPTB (53.1% vs 44.9%; aOR 1.22, 95% CI 1.22–1.79). For any given CL measured between 18 0–7 and 23 6/7 weeks, gestational age at delivery for monochorionic diamniotic pregnancies was about 2 weeks earlier compared to dichorionic pregnancies (MD -2.1 weeks; ANCOVA P < 0.001). Conclusion: Monochorionic diamniotic twin pregnancies had a higher rate of spontaneous preterm birth than dichorionic diamniotic pregnancies. The higher rate of spontaneous preterm delivery in monochorionic pregnancies is associated with lower midtrimester TVU CL when compared to dichorionic pregnancies.